Isolation of tissue-resident endothelial stem cells and their use in regenerative medicine - Tomohiro Iba; Hisamichi Naito; Shota Shimizu; Fitriana Nur Rahmawati; Taku Wakabayashi; Nobuyuki Takakura (BMC, 2019)
Abstract Background During sprouting angiogenesis, stalk cells, localized behind tip cells, generate endothelial cells (ECs) for the elongation of new vessels. We hypothesized that stalk cells may have endothelial progenitor cell properties because of their highly proliferative ability. We conducted Hoechst dye DNA staining in ECs of preexisting blood vessels from hind limb muscle and found that endothelial-side population (E-SP) cells, which efflux Hoechst rapidly with abundant ABC transporters, show highly producing ability of ECs. We previously showed the existence of E-SP cells in hind limb muscle, retina, and liver, but not in other tissues such as adipose tissue, skin, and placenta. Methods We investigated the existence of E-SP cells and analyzed their proliferative ability among CD31+CD45− ECs from adipose tissue, skin, and placenta of adult mice. We also analyzed the neovascular formation of E-SP cells from adipose tissue in vivo. Results We detected E-SP cells in all tissues examined. However, by in vitro colony formation analysis on OP9 cells, we found that E-SP cells from adipose tissue and skin, but not from placenta, have highly proliferative ability. Moreover, E-SP cells from adipose tissue could contribute to the neovascular formation in hind limb ischemia model. Conclusion The adipose tissue and skin are available sources to obtain endothelial stem cells for conducting therapeutic angiogenesis in regenerative medicine.